A 2D MOL passivated lead-free bismuth-based mixed halide perovskite nanodot and its preparation method and application

2D MOL passivated lead-free bismuth-based mixed halide perovskite nanodots were prepared by solvothermal and antisolvent recrystallization methods. The stability and activity of the perovskite nanodots were improved by interfacial chemical bonds, which solved the problems of photogenerated carrier recombination and instability in photocatalytic C(sp3)-H bond activation and achieved highly efficient selectivity of oxidation products.

CN117070217BActive Publication Date: 2025-10-28HUNAN UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310688347.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-12
Publication Date
2025-10-28
Estimated Expiration
2043-06-12

AI Technical Summary

Technical Problem

Existing lead-free halide perovskites suffer from problems such as rapid recombination of photogenerated carriers, instability, and excessive oxidation of products due to oxygen-active species in photocatalytic C(sp3)-H bond activation. Doping and heterojunction designs also suffer from poor universality and insufficient stability.

Method used

2D MOL ultrathin nanosheets were synthesized by solvothermal synthesis, and CSBB-X-ZrTATB was dispersed by interfacial chemical bonds. 2D MOL passivated lead-free bismuth-based mixed halide perovskite nanodots were prepared by antisolvent recrystallization to form interfacial chemical bonds to improve the exposure of active sites and the separation efficiency of photogenerated holes.

Benefits of technology

This improved the stability and catalytic activity of perovskite nanodots, enhanced the selectivity of oxidation products and the activity of the catalyst, and achieved efficient C(sp3)-H bond activation under green and mild conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117070217B_ABST
    Figure CN117070217B_ABST
Patent Text Reader

Abstract

This invention discloses a 2D MOL-passivated lead-free bismuth-based mixed halide perovskite nanodot, its preparation method, and its applications. It is synthesized by dispersing CSBB on ZrTATB in 2D MOL via interfacial chemical bonds. Its molecular formula is CSBB-X-ZrTATB, where X is the mass fraction of CSBB (0 < X ​​< 100%), and CSBB is perovskite Cs3Bi. 2‑ x Sb x Br9, 0 < x ≤ 0.4. This invention synthesizes 2D MOL ultrathin nanosheets via solvothermal synthesis. The solvothermal process allows for full coordination of 2D MOL with a perovskite precursor solution, followed by antisolvent recrystallization to obtain CSBB-X-ZrTATB, which exhibits excellent photocatalytic C(sp) content. 3 The activity and stability of the H-bond activation reaction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the fields of nanomaterial preparation and photocatalysis, specifically to a 2D MOL passivated lead-free bismuth-based mixed halide perovskite nanodots and their preparation method, and their application in photocatalysis of C(sp... 3 Applications in the activation of H-bonds. Background Technology

[0002] The selective oxidation activation of saturated CH bonds to prepare high-value-added oxygen-containing compounds is a challenging topic in synthetic chemistry. Traditional thermocatalytic activation is often limited by harsh reaction conditions, such as high temperature, high pressure, and the use of highly corrosive reagents. Under such harsh conditions, the partially oxidized products are more reactive than the corresponding hydrocarbons and are easily over-oxidized to acids or carbon dioxide, leading to reduced selectivity. In contrast, photocatalytic methods with active radicals hold promise for altering the activation pathway, lowering the activation barrier, and ultimately achieving C(sp) oxidation under green and mild conditions. 3 )-H bond activation. Lead-free halide perovskites show great potential in the photocatalytic conversion of aromatic hydrocarbons. Compared with most lead-free iodide halide perovskites, lead-free bromide and chloride perovskites with relatively positive valence band positions have stronger oxidation capabilities and are more favorable for photocatalytic C(sp)-H bond activation. 3 H-bond activation. As a low-toxicity and stable photocatalytic material, Cs3Bi2Br9 has gradually attracted researchers' attention in recent years. However, due to the rapid recombination of photogenerated carriers and the instability of Cs3Bi2Br9 in the environment, and the fact that the oxygen reactive species generated during the catalytic process of Cs3Bi2Br9 are superoxide radicals, the products are prone to over-oxidation, which is detrimental to improving product selectivity. Therefore, its photocatalytic activity needs further optimization. Doping and heterojunction design can achieve efficient electron transport and improve the activity and stability of perovskites. However, both methods still have problems. Doping is only suitable for the preparation of small amounts of elements, resulting in poor universality. Furthermore, heterojunctions formed through self-assembly have poor stability. Summary of the Invention

[0003] To address the problems existing in the prior art, the present invention aims to provide a 2D MOL-passivated lead-free bismuth-based mixed halide perovskite nanodot, its preparation method, and its application. 2D MOL ultrathin nanosheets are synthesized via solvothermal synthesis, and the 2D MOL is fully coordinated with the perovskite precursor solution using solvothermal methods. Antisolvent recrystallization yields CSBB-X-ZrTATB, exhibiting excellent photocatalytic C(sp) content. 3 The activity and stability of the )-H bond activation reaction.

[0004] To achieve the above-mentioned technical objectives, the present invention adopts the following technical solution:

[0005] A 2D MOL-passivated lead-free bismuth-based mixed halide perovskite nanodot is formed by dispersing CSBB on ZrTATB in 2D MOL via interfacial chemical bonds. Its molecular formula is CSBB-X-ZrTATB, where X is the mass fraction of CSBB (0 < X ​​< 100%), and CSBB is perovskite Cs3Bi. 2-x Sb x Br9, 0 < x ≤ 0.4.

[0006] Preferably, in the molecular formula, 25% ≤ X ≤ 90%; more preferably, 65% ≤ X ≤ 85%; and even more preferably, 70% ≤ X ≤ 80%.

[0007] This invention also provides a method for preparing the above-mentioned 2D MOL passivated lead-free bismuth-based mixed halide perovskite nanodots, comprising the following steps:

[0008] (1) Preparation of 2D MOL ZrTATB ultrathin nanosheets by a solvothermal method;

[0009] (2) The 2D MOL ZrTATB obtained in step (1) was ultrasonically dispersed in DMSO, and then CsBr, BiBr3 and SbBr3 were added. The precursor solution was obtained by solvothermal method.

[0010] (3) The precursor solution obtained in step (2) is added to isopropanol and crystallized by antisolvent method to obtain CSBB-X-ZrTATB.

[0011] As a preferred option, in step (1), the preparation process of 2D MOL ZrTATB ultrathin nanosheets is as follows: first, ZrOCl2·8H2O, DMF and glacial acetic acid are thoroughly mixed and reacted at 85℃ for 2h; then H3TATB is added, and the temperature is raised to 120℃ to continue the reaction for 12h to obtain 2D MOL ZrTATB ultrathin nanosheets.

[0012] Preferably, in step (2), the molar ratio of BiBr3 to SbBr3 is 1.7:0.3 to 1.9:0.1, and the concentration of CsBr in DMSO is 10 to 20 mM.

[0013] Preferably, in step (2), the solvothermal reaction conditions are: temperature 50-70°C and time 8-16h.

[0014] Preferably, in step (3), the volume ratio of the precursor solution to isopropanol is 1:20-30.

[0015] Preferably, in step (3), the antisolvent crystallization time is 0.5 to 5 minutes.

[0016] This invention also provides the application of the above-mentioned 2D MOL passivated lead-free bismuth-based mixed halide perovskite nanodots, using them for photocatalysis of C(sp... 3 -H bond activation reaction.

[0017] This invention utilizes 2D MOL ultrathin sheets to passivate perovskite with a small amount of Sb doping, and then synthesizes perovskite nanodots controllably via solvothermal and antisolvent recrystallization methods. This invention also anchors Bi in CSBBs using formic acid groups perpendicular to Zr-O clusters in 2D MOLs. +3 The controllable synthesis of perovskite nanodots was achieved through the interaction of interfacial chemical bonds, which improved the stability of the catalyst and the exposure of active sites. Furthermore, the ion channels formed by these interfacial chemical bonds enhanced the separation efficiency of photogenerated holes. Simultaneously, the interaction between 2D MOLs and perovskite transformed reactive oxygen species into singlet oxygen, thereby improving the selectivity of oxidation products.

[0018] Compared with the prior art, the advantages of the present invention are:

[0019] This invention prepares a CSBB-X-ZrTATB photocatalyst using a simple solvothermal pre-coordination and antisolvent recrystallization method. Controllable preparation of perovskite nanodots is achieved through the formation of interfacial chemical bonds, enhancing the exposure of active sites. Ion channels promote the separation efficiency of photogenerated carriers. The hydrophobicity of 2D MOLs reduces the wettability of perovskite to water, improving the stability of the perovskite material. The interaction between 2D MOLs and perovskite transforms reactive oxygen species into singlet oxygen, improving the selectivity of oxidation products. Attached Figure Description

[0020] Figure 1 SEM images of the samples prepared in Example 1(c), Comparative Example 1(b), and Comparative Example 2(a).

[0021] Figure 2 TEM images of the samples prepared in Example 1 (cg), Comparative Example 1 (b), and Comparative Example 2 (a).

[0022] Figure 3 The images show the XRD patterns of the samples prepared in Example 1, Comparative Example 1, and Comparative Example 2.

[0023] Figure 4 The graph shows a comparison of the catalytic performance of the samples prepared in Examples 1-4 and Comparative Examples 1-3.

[0024] Figure 5 The images show the free radical capture test and in-situ ESR characterization of the samples prepared in Example 1, Comparative Example 1, and Comparative Example 2 during the photocatalytic oxidation of toluene.

[0025] Figure 6The contact angle test diagrams are for the samples prepared in Example 1(b) and Comparative Example 2(a). Detailed Implementation

[0026] The present invention will be further described in detail below with reference to the embodiments, but the scope of protection of the present invention is not limited to these embodiments.

[0027] Comparative Example 1

[0028] 2D MOL ZrTATB ultrathin nanosheets were synthesized by solvothermal reaction. In a 20 mL capped glass bottle, 190 mg ZrOCl₂·8H₂O, 6 mL DMF, and 4 mL glacial acetic acid were added sequentially. After thorough mixing, the mixture was reacted in an oven at 85 °C for 2 h. Then, 44 mg H₃TATB was added, and the temperature was raised to 120 °C, and the reaction continued for 12 h. The solid was collected by centrifugation and washed three times sequentially with DMF and acetone. The solid material was dried in a vacuum oven at 60 °C for 12 h to obtain 2D MOL ZrTATB ultrathin nanosheets.

[0029] Example 1

[0030] The preparation of 2D MOL ZrTATB ultrathin nanosheets was the same as in Comparative Example 1.

[0031] 50 mg of ZrTATB was added to 30 mL of DMSO precursor solution containing 0.45 mmol CsBr, 0.075 mmol SbBr3, and 0.225 mmol BiBr3, and the mixture was ultrasonically dispersed for 2 h. The mixture was then stirred in an oil bath at 60 °C for 12 h. After cooling to room temperature, 2 mL of the precursor solution was added to 30 mL of isopropanol under vigorous stirring and stirred rapidly for 1 min. The mixture was washed three times with chloroform and dried in a vacuum oven at 60 °C for 12 h to obtain yellow CSBB-75-ZrTATB nanosheets.

[0032] Example 2

[0033] The preparation of 2D MOL ZrTATB ultrathin nanosheets was the same as in Comparative Example 1.

[0034] 450 mg of ZrTATB was added to 30 mL of DMSO precursor solution containing 0.45 mmol CsBr, 0.075 mmol SbBr3, and 0.225 mmol BiBr3, and the mixture was ultrasonically dispersed for 2 h. The mixture was then stirred in an oil bath at 60 °C for 12 h. After cooling to room temperature, 2 mL of the precursor solution was added to 30 mL of isopropanol under vigorous stirring and stirred rapidly for 1 min. The mixture was washed three times with chloroform and dried in a vacuum oven at 60 °C for 12 h to obtain yellow CSBB-25-ZrTATB nanosheets.

[0035] Example 3

[0036] The preparation of 2D MOL ZrTATB ultrathin nanosheets was the same as in Comparative Example 1.

[0037] 150 mg of ZrTATB was added to 30 mL of DMSO precursor solution containing 0.45 mmol CsBr, 0.075 mmol SbBr3, and 0.225 mmol BiBr3, and the mixture was ultrasonically dispersed for 2 h. The mixture was then stirred in an oil bath at 60 °C for 12 h. After cooling to room temperature, 2 mL of the precursor solution was added to 30 mL of isopropanol under vigorous stirring and stirred rapidly for 1 min. The mixture was washed three times with chloroform and dried in a vacuum oven at 60 °C for 12 h to obtain yellow CSBB-50-ZrTATB nanosheets.

[0038] Example 4

[0039] The preparation of 2D MOL ZrTATB ultrathin nanosheets was the same as in Comparative Example 1.

[0040] 17 mg of ZrTATB was added to 30 mL of DMSO precursor solution containing 0.45 mmol CsBr, 0.075 mmol SbBr3, and 0.225 mmol BiBr3, and the mixture was ultrasonically dispersed for 2 h. The mixture was then stirred in an oil bath at 60 °C for 12 h. After cooling to room temperature, 2 mL of the precursor solution was added to 30 mL of isopropanol under vigorous stirring and stirred rapidly for 1 min. The mixture was washed three times with chloroform and dried in a vacuum oven at 60 °C for 12 h to obtain yellow CSBB-90-ZrTATB nanosheets.

[0041] Comparative Example 2

[0042] 0.45 mmol CsBr, 0.075 mmol SbBr3, and 0.225 mmol BiBr3 were dissolved in 30 mL of DMSO to obtain a precursor solution. Then, 2 mL of the precursor solution was added to 50 mL of isopropanol under vigorous stirring for 1 min. The solution was washed three times with chloroform and dried in a vacuum oven at 60 °C for 12 h to obtain a yellow Cs3Bi 1.8 Sb 0.2 Br9 nanoparticles.

[0043] Comparative Example 3

[0044] The preparation of 2D MOL ZrTATB ultrathin nanosheets was the same as in Comparative Example 1.

[0045] Cs3Bi 1.8 Sb 0.2 The preparation of Br9 nanoparticles was the same as in Comparative Example 2.

[0046] 2D MOL ZrTATB ultrathin nanosheets and Cs3Bi 1.8 Sb 0.2Br9 nanoparticles were directly physically mixed at a mass ratio of 25:75 to obtain CSBB-75-ZrTATB-Mix.

[0047] Photocatalysis of C(sp) 3 The activation of the -H bond was used as a model reaction to investigate the catalytic activity of the prepared samples.

[0048] First, 5 mg of catalyst was dispersed in 2 mL of reaction substrate and subjected to three freeze-thaw cycles with liquid nitrogen. An oxygen bulb was then added (maintaining a pressure of 1 atm). The mixture was magnetically stirred in the dark for 30 min to introduce oxygen to the bottom of the reaction mixture, establishing adsorption-desorption equilibrium. A 300 W xenon lamp with a λ ≥ 400 nm filter was used as the light source, and illumination was applied for 2 h. Quantitative analysis was performed using gas chromatography with internal standard method. Quantification was conducted on a Shimadzu GC2010Plus chromatograph equipped with an FID detector and a WAX capillary column (30 m × 0.25 mm × 0.25 μm).

[0049] The results of the photocatalytic toluene oxidation reaction of the samples prepared in Examples 1-4 and Comparative Examples 1-2 are shown in Table 1:

[0050] Table 1. Results of photocatalytic toluene oxidation of samples obtained in Examples 1-4 and Comparative Examples 1-2

[0051]

[0052] As shown in Table 1, ZrTATB alone has no catalytic activity, and Cs3Bi alone... 1.8 Sb 0.2 The formation rates of benzaldehyde and benzyl alcohol by Br9 were only 3.373 mmol g. -1 h -1 and 0.437 mmol g -1 h -1 Furthermore, in-situ compounding of CSBB with MOL significantly enhanced catalytic activity, particularly the formation rates of benzaldehyde and benzyl alcohol by CSBB-75-ZrTATB, which were 14.481 mmol g / L. -1 h -1 and 2.006 mmol g -1 h -1 The photocatalytic effect is the best.

[0053] Table 2 shows the results of the photocatalytic toluene oxidation reaction of the samples prepared in Example 1 and Comparative Example 3.

[0054]

[0055]

[0056] As shown in Table 2, the toluene conversion rate of CSBB-75-ZrTATB formed through interfacial chemical bonds is significantly higher than that of CSBB-75-ZrTATB-Mix obtained by simple physical mixing. The formation rates of benzaldehyde and benzyl alcohol in CSBB-75-ZrTATB-Mix are 8.330 mmol g and 8.330 mmol g, respectively. -1 h -1 and 1.214 mmol g -1 h -1 .

[0057] Using CSBB-75-ZrTATB prepared in Example 1, toluene derivatives with other substituents were tested, and the results are shown in Table 3:

[0058] Table 3. Results of photocatalytic oxidation of toluene derivatives in the samples prepared in Example 1.

[0059]

[0060] Note: a Reaction conditions: 2 mL substrate, 5 mg CSBB-75ZrTATB as photocatalyst, λ≥400 nm, O2 1 atm, reaction time 3 h. b Solid p-nitrotoluene (1.29 g, relative density 1.29 g / mL) -1 Dissolve in 2.5 mL of acetonitrile and react.

[0061] like Figure 1 As shown in the SEM, Figure 1 (a)Cs3Bi 1.8 Sb 0.2 Br9 exists in large, blocky forms. Figure 1 (b) ZrTATB consists of ultrathin nanosheets with a thickness of approximately 4 nm. Figure 1 (c) is CSBB-75-ZrTATB and Figure 1 (b) have similar shapes, both being ultrathin nanosheets, and a small amount of perovskite can be seen with small size, indicating that the combination of 2D MOL and perovskite effectively passivates the perovskite and avoids the perovskite from accumulating into large lumps.

[0062] like Figure 2 As shown in the TEM, (a) Cs3Bi 1.8 Sb 0.2Br9 also exists in large bulk form. (b) ZrTATB is an ultrathin nanosheet. (c) It is difficult to see perovskite material in CSBB-75-ZrTATB. By local magnification of its surface, perovskite nanodots appeared (e), indicating that perovskite nanodots can be prepared controllably on 2D MOL through the action of interfacial chemical bonds. High-magnification transmission electron microscopy shows that the perovskite is mainly composed of (112)(003)(201) crystal planes (f), further confirming the existence of perovskite in the form of nanodots on MOL. Elemental distribution confirms that the elements are uniformly distributed in the selected area (g).

[0063] like Figure 3 XRD characterization, compared with the simulation plot of ZrTATB, confirms the success of ZrTATB. CSBB(Cs3Bi 1.8 Sb 0.2 The comparison of Br9 with standard cards of CSB (Cs3Sb2Br9) and CBB (Cs3Bi2Br9) also confirmed the successful synthesis of CSBB, further confirming the successful synthesis of CSBB-75-ZrTATB.

[0064] like Figure 4 Performance comparison tests showed that the catalytic performance was best with a CSBB content of 75 wt%. Pure ZrTATB had no catalytic activity, and CSBB exhibited low catalytic activity, with a toluene conversion rate of only 3.810 mmol / h. -1 g -1 The activity of CSBB-75-ZrTATB after binding with 2D MOL was higher than that of CSBB alone, with the toluene conversion rate reaching as high as 16.487 mmol / h. -1 g -1 The possible reasons are: the formic acid groups on the surface of 2D MOL form strong ionic bonds with the perovskite, stabilizing the perovskite and constructing ion channels that accelerate the generation of photogenerated electrons and holes; on the other hand, the passivation effect of 2D MOL reduces the size of the perovskite, exposing more active sites. The hydrophobicity of 2D MOL reduces the water wettability of the perovskite, enhancing the optical stability of the perovskite. Figure 6 In the cyclic experiment, the catalyst activity hardly decreased after six cycles, further confirming that 2D MOL enhances the stability of perovskite through interfacial chemical bonds.

[0065] like Figure 5 As shown, singlet oxygen was found to be the main oxygen reactive species through free radical capture (a), while free radical capture of CSBB showed that superoxide radical was the main oxygen reactive species. Further in-situ ESR detection revealed that neither single CSBB (c) nor ZrTATB (b) could produce singlet oxygen, but they produced singlet oxygen after being combined through interfacial chemical bonds (d).

Claims

1. A 2D MOL-passivated lead-free bismuth-based mixed halide perovskite nanodot, characterized in that: It is formed by dispersing CSBB on ZrTATB in a 2D molecular matrix via interfacial chemical bonds, with the molecular formula CSBB-X-ZrTATB, where X is the mass fraction of CSBB, 0 < X ​​< 100%, and CSBB is perovskite Cs3Bi. 2-x Sb x Br9, 0 < x ≤ 0.

4.

2. The 2D MOL passivated lead-free bismuth-based mixed halide perovskite nanodots according to claim 1, characterized in that: In the stated molecular formula, 25% ≤ X ≤ 90%.

3. The 2D MOL passivated lead-free bismuth-based mixed halide perovskite nanodots according to claim 2, characterized in that: In the stated molecular formula, 65% ≤ X ≤ 85%.

4. The method for preparing 2D MOL passivated lead-free bismuth-based mixed halide perovskite nanodots according to any one of claims 1-3, characterized in that: Includes the following steps: (1) Preparation of 2D MOL ZrTATB ultrathin nanosheets by a solvothermal method; (2) The 2D MOL ZrTATB obtained in step (1) was ultrasonically dispersed in DMSO, and then CsBr, BiBr3 and SbBr3 were added. The precursor solution was obtained by solvothermal method. (3) The precursor solution obtained in step (2) is added to isopropanol and crystallized by antisolvent method to obtain CSBB-X-ZrTATB.

5. The preparation method according to claim 4, characterized in that: In step (1), the preparation process of 2D MOL ZrTATB ultrathin nanosheets is as follows: ZrOCl2·8H2O, DMF and glacial acetic acid are thoroughly mixed and reacted at 85℃ for 2h; then H3TATB is added, and the temperature is raised to 120℃ and the reaction is continued for 12h to obtain 2D MOL ZrTATB ultrathin nanosheets.

6. The preparation method according to claim 4, characterized in that: In step (2), the molar ratio of BiBr3 to SbBr3 is 1.7:0.3 to 1.9:0.1, and the concentration of CsBr in DMSO is 10 to 20 mM.

7. The preparation method according to claim 4, characterized in that: In step (2), the solvothermal reaction conditions are: temperature 50-70℃, time 8-16h.

8. The preparation method according to claim 4, characterized in that: In step (3), the volume ratio of the precursor solution to isopropanol is 1:20-30.

9. The preparation method according to claim 4, characterized in that: In step (3), the antisolvent crystallization time is 0.5 to 5 minutes.

10. The application of the 2D MOL passivated lead-free bismuth-based mixed halide perovskite nanodots according to any one of claims 1-3 or the 2D MOL passivated lead-free bismuth-based mixed halide perovskite nanodots prepared by the preparation method according to any one of claims 4-9, characterized in that: Use it for photocatalysis of C(sp) 3 -H bond activation reaction.

Citation Information

Patent Citations

  • Lead-free bismuth-based mixed halogenated perovskite nanosheet as well as preparation method and application thereof

    CN112892561A

  • Application of inverse opal phase perovskite Cs3BixSb (2-x) Br9 in EDOT photocatalytic polymerization

    CN113980249A